2008
DOI: 10.1016/j.jaci.2008.06.021
|View full text |Cite
|
Sign up to set email alerts
|

12/15-Lipoxygenase deficiency protects mice from allergic airways inflammation and increases secretory IgA levels

Abstract: Background-Induction of 15-lipoxygenase-1 (15-LO-1) has been observed in the airways of subjects with asthma, although its physiologic role in the airways has remained largely undefined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…E1 in Ref. 24), these data suggest that 15(S)-HETE is also partially produced from non-12/ 15-LOX sources in our culture systems.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…E1 in Ref. 24), these data suggest that 15(S)-HETE is also partially produced from non-12/ 15-LOX sources in our culture systems.…”
Section: Discussionsupporting
confidence: 61%
“…Although recent studies have suggested that products of the 12/ 15-LOX biosynthetic pathway may contribute to allergic airway inflammation (24,34), these studies are confounded by the use of 12/15-LOX Ϫ/Ϫ mice in which the deficiency in 12/15-LOX stimulates a default pathway that channels arachidonic acid through the 5-LOX pathway with subsequent up-regulation of proinflammatory cysteinyl leukotrienes (24,35). Additionally, it is likely that 12/15-LOX Ϫ/Ϫ mice are deficient in a complex mixture of lipid mediators that mediate both pro-and anti-inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…High mucosal SIgA levels could possibly interfere with the interaction between allergen and IgE antibodies in sensitized individuals, thereby preventing triggering of allergic inflammation and clinical symptoms. This notion is supported by animal models showing that mucosal IgA responses inhibit airway reactivity in sensitized mice (27)(28)(29). Also, induction of IgA to allergens during immunotherapy has been suggested to relate to the development of tolerance (30).…”
Section: Discussionmentioning
confidence: 89%
“…16 Interestingly, after allergen exposure, Alox15 knockout mice had a markedly decreased number of eosinophils and did not produce specific IgE antibodies. 17 This suggests that ALOX15 activity is required for the development of sensitization during asthma. Although the significance of increased expression of ALOX15 in patients with eosinophilic esophagitis is currently unknown, it is possible that it has a role in allergen sensitization similar to that in asthma.…”
Section: A Matoso Et Almentioning
confidence: 99%